German Children's Use of Word Order and Case Marking to Interpret Simple and Complex Sentences: Testing Differences Between Constructions and Lexical Items. Issue 2 (2nd April 2016) - Brandt, Silke; Lieven, Elena; Tomasello, Michael
ABSTRACT: Children and adults follow cues such as case marking and word order in their assignment of semantic roles in simple transitives (e.g., the dog chased the cat ). It has been suggested that the same cues are used for the interpretation of complex sentences, such as transitive relative clauses (RCs) (e.g., that's the dog that chased the cat ) (Bates, Devescovi, & D'Amico, 1999). We used a pointing paradigm to test German-speaking 3-, 4-, and 6-year-old children's sensitivity to case marking and word order in their interpretation of simple transitives and transitive RCs. In Experiment 1, case marking was ambiguous. The only cue available was word order. In Experiment 2, case was marked on lexical NPs or demonstrative pronouns. In Experiment 3, case was marked on lexical NPs or personal pronouns. Whereas the younger children mainly followed word order, the older children were more likely to base their interpretations on the more reliable case-marking cue. In most cases, children from both age groups were more likely to use these cues in their interpretation of simple transitives than in their interpretation of transitive RCs. Finally, children paid more attention to nominative case when it was marked on first-person personal pronouns than when it was marked on third-person lexical NPs or demonstrative pronouns, such as der Löwe 'the-NOM lion' or der 'he-NOM.' They were able to successfully integrate this case-marking cue in their sentence processing even when it appeared late in the sentence. We discuss four potential reasons for these differences across development, constructions, and lexical items. (1) Older children are relatively more sensitive to cue reliability. (2) Word order is more reliable in simple transitives than in transitive RCs. (3) The processing of case marking might initially be item-specific. (4) The processing of case marking might depend on its saliency and position in the sentence.